Reporting Security: Postcolonial Governmentality in the United Nations' Trusteeship System. Issue 1 (8th October 2021) - Bonacker, Thorsten
Abstract: This article examines the political rationality and governance practices that emerged in the course of the international politics of decolonization. It focuses primarily on the UN trusteeship system, within which the former League of Nations mandates were continued by the trusteeship powers. In this process, the trustees' policies were placed under international scrutiny. The article ties in with International Political Sociology's increased interest in historical perspectives. In particular, it asks how the political rationality of the trusteeship system differs from colonial governmentality. Two arguments are put forward: first, international governing, as can be seen from the trusteeship system, is characterized by a postcolonial governmentality that continues central elements of colonial governmentality, but transfers them to the international level. Second, following Latour, it is argued that trusteeship governance is constituted by forms of knowledge production and the bureaucratic circulation of information that continue to shape the governance of international organizations today. To this end, the article takes up in particular the reporting system of the trusteeship system as well as its central instruments of knowledge production: the visiting missions, the petition system, and the collection of data through questionnaires.